Path for Ukraine's Economic Growth : Technology Upgrading - World Bank (World Bank, Washington, DC, 2019)
This report examines Ukraine's economic decline and development through the lens of technology upgrading. The technology upgrading framework assumes that economic growth is a function of technology capability, whereby upgrading occurs through technological, industrial, and organizational change. This technology upgrading framework is applied to analyze the Ukrainian economy, which reflects its limited capability to generate, as well as absorb, new technology. The report finds that Ukraine ranks last among comparison countries in a composite index of technology upgrading, with especially low performance in terms of production, management, and R&D capabilities. A case study on Ukraine's booming ICT sector, Ukraine's fastest-growing sector, showcases the country's potential, while simultaneously demonstrating which factors and capabilities can constrain its future growth. While Ukraine has developed a vibrant ICT industry, significant challenges exist for its long-term success. To address the challenges, three main areas for policy action are recommended. These include: (1) the development of firms' managerial capabilities and adoption of productivity-enhancing technologies, (2) better integration into global value chains, and (3) supply and retention of a digital-ready workforce. The report also offers cross-cutting recommendations for improving Ukraine's business environment and the complementarities needed for firms’ growth and upgrading.